1993
DOI: 10.1128/mcb.13.2.869
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a 60-kilodalton stress-related protein, p60, which interacts with hsp90 and hsp70.

Abstract: Immunoaffinity purification of hsp90 from chick oviduct cytosol reveals two major proteins, hsp70 and a 60-kDa protein (p60), copurifying with hsp90. A similar result is obtained when hsp90 is immunoaffinity purified from chick liver and brain cytosols, avian fibroblasts, and rabbit reticulocyte lysate. This p60 is the same protein previously identified in certain assembly complexes of chick progesterone receptor generated in a cell-free reconstitution system. Tryptic and cyanogen bromide peptide fragments wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
200
0
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(208 citation statements)
references
References 57 publications
7
200
0
1
Order By: Relevance
“…HOP, Hsp70-Hsp90 Organizing Protein, a 60 kDa protein (also called Sti1 or p60 in yeast) was first identified in a genetic screen to play a role in heat shock response of some Hsp70 genes (Nicolet and Craig, 1989;Smith et al, 1993). Subsequently, it was shown that HOP is a functional homolog of the BAG-1 protein that stimulates nucleotide exchange by Hsp70 (Gross and Hessefort, 1996).…”
Section: Ii41121 the Hsp70 Chaperone Systemmentioning
confidence: 99%
“…HOP, Hsp70-Hsp90 Organizing Protein, a 60 kDa protein (also called Sti1 or p60 in yeast) was first identified in a genetic screen to play a role in heat shock response of some Hsp70 genes (Nicolet and Craig, 1989;Smith et al, 1993). Subsequently, it was shown that HOP is a functional homolog of the BAG-1 protein that stimulates nucleotide exchange by Hsp70 (Gross and Hessefort, 1996).…”
Section: Ii41121 the Hsp70 Chaperone Systemmentioning
confidence: 99%
“…Hop/STI1 (Hsp-organizing protein/stress-inducedphosphoprotein 1) is a key scaffold protein, which mediates client transfer from Hsp70 to Hsp90 in the later stages of client maturation (Smith et al 1993;Chen and Smith 1998). Initially, client proteins complex with Hsp40 and Hsp70 (Hernandez et al 2002;Pratt and Toft 2003).…”
Section: Biological Contextmentioning
confidence: 99%
“…p23, so named for its apparent molecular weight on SDS-PAGE gels, is an ~ 18 kDa protein of wide tissue distribution, which is highly conserved throughout eukaryotes, p23 was first observed as a component of the cytoplasmic form of the avian progesterone receptor (PR) complex [24], but it has also been found associated with the 90 kDa heat shock protein, hsp90 [25].…”
Section: Binding Of the Mtase To P23 In Vitromentioning
confidence: 99%